Neuroendokrinní nádory trávicího ústrojí--historie a soucasnost - Mandys, V (Ceskoslovenska patologie, 2009)
Histological classification of the neuroendocrine tumours ("carcinoids") of the alimentary tract, as well as the opinion on biological behaviour of these tumours, changed rapidly within the last decade. Advances in knowledge of cellular biology of the diffuse endocrine system and in clinical diagnostics and treatment of tumours lead to the creation of a new histological classification of neuroendocrine tumours. This classification, apart from essential histological picture and immunohistological characterisation of the markers of neuroendocrine differentiation, also includes definition of biological properties of tumours based on their site of origin, mitotic and proliferative activity of the tumour cells and clinicopathological correlation, including the size of the tumour and its progression. Exact classification of an individual tumour into a corresponding category is an essential condition to select adequate following diagnostic procedures and optimal therapeutic strategy.
Keywords: Neuroendocrine Tumors; Digestive System Neoplasms; lidé; nádory trávicího systému; neuroendokrinní nádory; Humans